x + x 2 + x 3 + x 4 + . . . = 9 9 9
Find the value of x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Simple standard approach.
Why is x + x 2 + x 3 + . . . = 1 − x x ?
Log in to reply
Since it is an infinite geometric with first term x and common ratio x .
Here is the easy way to find x by factoring:
x + x 2 + x 3 + x 4 + . . . = 9 9 9
x [ 1 + ( x + x 2 + x 3 + x 4 + . . . ) ] = 9 9 9
x ( 1 + 9 9 9 ) = 9 9 9
1 0 0 0 x = 9 9 9 → x = 1 0 0 0 9 9 9
If ∣ x ∣ < 1
a 1 + a 1 x + a 1 x 2 + a 1 x 3 + ⋯ = 1 − x a 1
⇒
1 + x + x 2 + x 3 + ⋯ = 1 − x 1
x + x 2 + x 3 + ⋯ = 1 − x 1 − 1
⇒
1 − x 1 − 1 = 9 9 9
1 0 0 0 − 1 0 0 0 x = 1
9 9 9 = 1 0 0 0 x
∴ x = 1 0 0 0 9 9 9
simply a geometric sequence
Problem Loading...
Note Loading...
Set Loading...
First, we should know that the validity of this infinite expansion is only when ∣ x ∣ < 1 . Let us check that out.
x + x 2 + x 3 + … = 1 − x x 9 9 9 = 1 − x x x = 1 0 0 0 9 9 9
So, this is true, since it is less than 1 .
So, the answer is 1 0 0 0 9 9 9 .